Outcome of Early versus Late Tracheostomy in Neurosurgical critical Patient - Neupane, Bal Ram; Lamichhane, Anita (Nepal Journal of Neuroscience, 2019)
The Study was conducted to evaluate the effectiveness of early tracheostomy and of late tracheostomy in neurosurgical critical patients. A retrospective chart review of Neurosurgical critical patients who underwent Tracheostomy from September 2017 to March 2019. Patients were divided into two groups: early tracheostomy occurring within 7 days and late tracheostomy after 7 days of mechanical ventilation. Two groups were compared in terms of days under ventilation, Complication and outcome. There were 30 patients over 18 month period. Age range from 18years to 86 years with means of 52.93±16.59 years. Male: Female ratio was 3:1. 12 (40%) had Early tracheostomy (ET) and 18 (60%) had Late tracheostomy (LT). Day on ventilation on ET group was 14.8±10.25 while on LT group was 20±8.4.Procedure related complication were more common in Late tracheostomy group with 11.11% and 16.66% tracheostomy site hematoma and pneumonia respectively, and subcutaneous emphysema were 8.33% of LT versus a 5.55% of ET, Stomal site infection were 11.11% in late tracheostomy versus 8.33% in ET. Early tracheostomy compare to late tracheostomy reduces the days on Mechanical ventilation, the ICU length of stay, hospital stay and procedural related complication, but it does not affect the mortality rate.